Marginalisasi perempuan dalam pernikahan di kalangan mahasiswa Universitas Islam Negeri (UIN) Imam Bonjol Padang - Susilawati Susilawati; Try Bunga Firma (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
This study aims to analyze the phenomenon of marriage among female university students. This study focuses on discussing the dual role and gender inequality of female students at the State Islamic University (UIN) Imam Bonjol Padang. The approach in this study uses a gender bias approach and feminism. The research method used in this research is descriptive qualitative involving several key informants. The data sources in this study were obtained from direct observation (observation), interviews, literature studies and documentation. The findings of this study indicate that the roles and responsibilities experienced by female students simultaneously have had a negative impact on academic life in the form of continuing education in lectures that are not on target and on home life due to self-preparation, proper time management, mental unpreparedness, and unpreparedness. The economy causes a negative impact on women themselves because of their involvement in meeting household needs, so this reality can be a trigger for the birth of conflict and the marginalization of women.